Boosting Ge-Epi P-Well Mobility & Crystal Quality with Si or Sn Implantation and Melt Annealing. (20th July 2018) - Borland, John O; Chaung, Shang-Shuin; Tseng, Tseung-Yuen; Joshi, Abhijeet; Basol, Bulent; Lee, Yao Jen; Kuroi, Takashi; Tabata, Toshiyuki; Huet, Karim; Goodman, Gary; Khapochkina, Nadya; Buyuklimanli, Temel
Abstract : We investigated the effects of Si, Sn and cluster-C implantation into both P-well and N-well doped regions of Ge-epi on Si wafers after laser annealing. XRD analysis shows improved Ge-epi crystallinity after >1.5J/cm 2 laser melt annealing (liquid phase epitaxial regrowth) compared to sub-melt annealing (solid phase epitaxial regrowth). For the P-well case the Ge-epi Rs decreased to 1, 600Ω/□ compared to Si at 3, 400Ω/□ suggesting a hole mobility increase of 2.1x from 150cm 2 /V-s to 315cm 2 /V-s but actual measured Hall mobility was 650cm 2 /V-s to a depth of 60nm, an increase of 4.3x. The 1.8J/cm 2 laser melt anneal with Si implant improved mobility uniformly to 700cm 2 /V-s to a depth of 100nm while Sn implant improved mobility to 900cm 2 /V-s from the Ge-epi surface to a depth of 70nm then increases to 3000cm 2 /V-s at a depth of 100nm. Measuring mobility depth profiles can be very critical in engineering surface and bulk mobility improvements which can be determined by chemical compositional changes in the Ge-epilayer especially for C where no liquid phase diffusion or movement could be detected.